Penerapan Metode E-Learning Dalam Pembelajaran Seni Budaya (Tari) Kelas XI MIA Di SMA Dian Andalas Padang - Yonela Putri Agustin; Fuji Astuti (FBS Universitas Negeri Padang, 2021)
This research aims to see the application of online methods in the learning of cultural arts (dance) class XI MIA at SMA Dian Andalas Padang. The type of research used is qualitative research with descriptive methods. The instruments in this study are the researchers themselves and assisted with supporting instruments in the form of documentation from the recording tools in the field. Evaluation of learning outcomes consists of knowledge (cognitive) and skills (psychomotor). Data collection techniques are carried out by means of library studies, observations and documentation. The steps to analyze data are data collection, clarifying data and making conclusions. The results showed that the application of online methods in cultural art learning class XI MIA at Sma Dian Andalas Padang is quite good. This can be seen from the planning and implementation of learning carried out by cultural arts teachers. However, judging by the students' grades there are some students who have grades less than KKM in practical learning. Meanwhile, on cognitive understanding each student gets good results. The provision of practical materials at the second meeting with the giving of demonstration videos makes students less able to imitate the given movement by reaching an average of 80.5 with good criteria. Meanwhile, on the provision of cognitive materials at the third meeting with the provision of knowledge tests in cultural arts learning with online methods already running by reaching an average of 94.5 with excellent criteria.